EXPERIMENTAL INVESTIGATION AND DEVELOPMENT OF MATHEMATICAL CORRELATIONS OF CUTTING PARAMETERS FOR MACHINING GRAPHITE WITH CNC WEDM (Journal of Mechanical Engineering, 2009)
The Wire cut electrical discharge machining is found to have tremendous potential in the present day metal cutting process, for achieving improved geometric features of work pieces, dimensional accuracy, surface finish etc. Improving the productivity in CNC WEDM depends solely on optimization of various process parameters viz... discharge current, thickness etc. Thus the present work is aimed at experimental evaluation of those machining parameters for different sizes of Graphite which is a prominent electrode material. Further the effect of these parameters on cutting speed, spark gap and material removal rate is investigated and best suited values are obtained for stable and controlled machining with least wire breakage. Based on the experimental results, empirical correlations are established and validated to evaluate the above parameters analytically for different work piece sizes. The correlations are found useful for finding the best suited discharge current, spark gap, cutting speed and cutting time under various cutting conditions. The results are represented in graphical form also. Key Words: WEDM, Cutting speed, MRR, Spark gap, Mathematical correlations   doi: 10.3329/jme.v40i1.3474 Journal of Mechanical Engineering, Vol. ME40, No. 1, June 2009 63-67